Sistem Berbasis Website Untuk Koreksi Soal Esai Dengan Association Rules - Teguh Arlovin; Bayu Pangestu (Jurnal Media Infotama, 2025)
This research aims to design and implement an automatic essay correction system based on a website by applying the Association Rules algorithm. The system is developed using PHP, MySQL, HTML, and CSS to provide an accessible and user-friendly platform. Data were collected from 30 high school students, while teachers acted as validators of the system’s assessment. The system was tested using black box testing and performance comparison between manual and automatic correction. The results show that the system achieved an accuracy rate of 86% compared to manual correction, with an efficiency improvement of 55% faster. These findings indicate that the developed system can reduce teachers’ workload, provide more consistent evaluations, and support the digital transformation of learning assessments. The research concludes that Association Rules can be effectively applied in the education domain, especially for essay-based evaluations.